Distributional Impacts of COVID-19 in the Middle East and North Africa Region - Hoogeveen, Johannes G.; Lopez-Acevedo, Gladys (Washington, DC: World Bank, 2021)
COVID-19 is one of multiple crises to have hit the Middle East and North Africa (MENA) region in the decade following the Arab Spring. War, oil price declines, economic slowdowns and now a pandemic are tearing at the social fabric of a region characterized by high rates of unemployment, high levels of informality and low annual economic growth. The economic costs of the pandemic are estimated at about $227 billion, and fiscal support packages across MENA are averaging 2.7 percent of GDP, putting pressure on already weak fiscal balances and making a quick recovery challenging. Pre-pandemic MENA was the only region in the world experiencing increases in poverty and declines in life satisfaction. This Report investigates how COVID-19 changed the welfare of individuals and households in the region. It does so by relying on phone surveys implemented across the region and complements these with micro-simulation exercises to assess the impact of COVID-19 on jobs, income, poverty and inequality. The two approaches perform a complementary task by corroborating each other’s results, thereby making the findings more robust and richer. This Report’s results show that in the short run, poverty rates in MENA will increase significantly, and that inequality will widen. A group of “new poor” is likely to emerge that may have difficulty to recover from the economic consequences of the pandemic. The Report adds value by analyzing newly gathered primary data, along with projections based on newly modelled micro-macro simulations and by identifying key issues that policy makers should focus on to enable a quick, inclusive and sustained economic recovery.